Up in smoke - Brooks, Nick, 1989- (Henry Holt and Company, 2025)
After Cooper King is pressured by big brother figure Jason to go on a looting spree during a local march, the unthinkable happens: gunshots ring in the air and someone ends up dead. After Cooper flees, the news shows four teens in ski masks near the scene of the murder -- Cooper and his friends. Cooper fears the cops will come knocking at his door, and the pressure only mounts when a suspect is taken into custody: Jason. Monique, Jason's sister and Cooper's longtime crush, is willing to go any length to clear her brother's name. Even if she needs to go into the belly of the beast and confront the killer herself. When she teams up with Cooper, they fall down the investigation rabbit hole and start to fall for each other. But little does Monique know that within this web of deception, Cooper is shrouding the truth that he was there when the shots went off. If the pair fail to uncover the real murderer, Jason will get locked up for a crime he didn't committ -- and drag down Cooper with him.